The essential feature to leverage retargeting effectiveness in online advertising - A Facebook and Instagram case study - Reis, Maria Marta Terras de Melo Moreira dos (2021)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence